Self‐aligning subatmospheric hybrid liquid junction electrospray interface for capillary electrophoresis. Issue 3 (29th September 2015) - Krenkova, Jana; Kleparnik, Karel; Grym, Jakub; Luksch, Jaroslav; Foret, Frantisek
Abstract : We report a construction of a self‐aligning subatmospheric hybrid liquid junction electrospray interface for CE eliminating the need for manual adjustment by guiding the capillaries in a microfabricated liquid junction glass chip at a defined angle. Both the ESI and separation capillaries are inserted into the microfabricated part until their ends touch. The distance between the capillary openings is defined by the angle between the capillaries. The microfabricated part contains channels for placement of the capillaries and connection of the external electrode reservoirs. It was fabricated using standard photolithographic/wet chemical etching techniques followed by thermal bonding. The liquid junction is connected to a subatmospheric electrospray chamber inducing the flow inside the ESI needle and helping the ion transport via aerodynamic focusing.